Conservation of Modern Oil Paintings - van den Berg, Klaas Jan.; Bonaduce, Ilaria; Burnstock, Aviva; Ormsby, Bronwyn; Scharff, Mikkel; Carlyle, Leslie; Heydenreich, Gunnar; Keune, Katrien; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Artists' oil paints have become increasingly complex and diverse in the 20th Century, applied by artists in a variety of ways. This has led to a number of issues that pose increasing difficulties to conservators and collection keepers. A deeper knowledge of the artists' intent as well as processes associated with material changes in paintings is important to conservation, which is almost always a compromise between material preservation and aesthetics. This volume represents 46 peer-reviewed papers presented at the Conference of Modern Oil Paints held in Amsterdam in 2018. The book contains a compilation of articles on oil paints and paintings in the 20th Century, partly presenting the outcome of the European JPI project 'Cleaning of Modern Oil Paints'. It is also a follow-up on 'Issues in Contemporary Oil Paint' (Springer, 2014). The chapters cover a range of themes and topics such as: patents and paint manufacturing in the 20th Century; characterization of modern-contemporary oil paints and paint surfaces; artists' materials and techniques; the artists' voice and influence on perception of curators, conservators and scientists; model studies on paint degradation and long term stability; approaches to conservation of oil paintings; practical surface treatment and display. The book will help conservators and curators recognise problems and interpret visual changes on paintings, which in turn give a more solid basis for decisions on the treatment of these paintings. .
Challenges in research: Connecting scientific analysis with conservation practice -- Evaluating cleaning systems for use on water sensitive modern oil paints: a comparative study -- Paint Technology -- Pigment Surface Treatments: 20th and 21st century industrial techniques and strategies for their detection -- Meet the future: the creation of new pigments -- Zinc oxide in oil-based house paint: Insights from a paint chemist's notebook dated 1949 -- A Glimpse into the House and Decorative Paint Market in Norway During World War I (1914-1918) -- Approaches to the identification of Royal Talens' ETA (emulsion) paint in objects of art -- Synthetic organic pigments in Royal Talens oil paint 1920-1950 - The case of vermillion imit -- Case studies: artists techniques and materials; degradation; ethical considerations; treatment options -- Ellsworth Kelly: The Studio and Beyond -- A new vocabulary of color: Bocour oil paints and Barnett Newman -- Analysis of Modern Paints and Conservation at the Clyfford Still Museum -- Pigments of Soviet Artists in the 1950s - late 70s -- A View Through the Meander: A Study of Knifer's Oil Paintings from the 1960s -- Preservation of Russian Abstract Art of the Second Part of the 20th Century -- Investigating colour changes in red and blue paints - a preliminary study of art materials and techniques in Edvard Munch's Old Man in Warnemünde (1907) -- Aspects of Lovis Corinth's Painting Technique in his late Work: Working Process and Colour Structure captured in Paint and on Film -- Oil paint straight from the tube: paint-specific deterioration in works by Alexis Mérodack-Jeaneau, 1910-1913 -- Picasso 1917: Failure Mechanisms in the Paint Layers of Four Artworks -- Investigation on the speckles syndrome affecting late 1920s oil paintings by René Magritte -- Diagnosis and conservation process of major curled-up delaminated areas in a black oil painting from 1960 by Pierre Soulages.-Examination of paint delamination in C'est grace à nous by Asger Jorn -- A synchrotron photoluminescence microscopy study into the use and degradation of zinc white in The Woodcutters by Bart van der Leck -- 'Breaking waves'. The relation between zinc-oxide degradation in a ground layer and extreme delamination on Beach Scene, by J.E.H. Akkeringa (1861-1942) -- Efflorescence on the paintings of Edwin Austin Abbey: Examination, analysis, and cleaning of surface bloom on The Spirit of Light -- A Study of Softening and Liquefying Oil Paint on Womenizer by Alex Janvier; K. Helwig et al -- The Deterioration and Treatment of Some Late Paintings by Paul-Émile Borduas -- Colors before Zero: commercial alkyd-oil enamel paints in early reliefs by Jan J. Schoonhoven -- Some considerations when cleaning Robert Ryman's oil paint(ings) -- Challenges of Surface Cleaning Paintings by Asger Jorn (1914-1973): An Inventory of Existing Practice.-Decision-making processes regarding the treatment of modern oil paintings (1950's - present) exhibiting paint dripping and oil exudates -- Between rejection, ignorance, and preference: The history and dilemma of modern double-sided (recto/verso) paintings with regard to issues of conservation and presentation -- Model studies -- Novel microscopic strategy for the study of paint cross-sections -- Investigations into the mechanical properties of commercial artists' oil paint by Dynamic Mechanical (Thermal) Analysis (DMA), Nanoindentation (UNHT), and Dynamic Vapour Sorption (DVS) -- A Preliminary Investigation into the Behavior of Modern Artists' Oil Paints in a Hot and Humid Climate -- Inside the forger's oven: identification of drying products in oil paints during and after accelerated drying with increased temperatures -- The influence of metal stearates on the water sensitivity of modern oil paints -- The rate of solvent action on modern oil paint -- Conservation treatment -- Water-sensitivity in modern oil paintings: Trends in phenomena and treatment options -- Modern oil paintings in Tate's collection: a review of analytical findings and reflections on water sensitivity; -- Analytical study to monitor the effectiveness of a combined liquid-dispensing and micro-aspiration system for the cleaning of modern oil paintings -- Ketone resins varnishes on canvas paintings from the collection of the Munch Museum -- Designing mock-up paintings for a study of novel surface cleaning techniques for Munch's unvarnished Aula paintings -- Analysis of cleaning efficacy and clearance of silicone-based Pickering-type emulsions used in the cleaning of water-miscible oil paints -- Improving the surface cleaning of water sensitive oil paint by use of alternative application methods; M. Hintz et al -- Evolon® CR microfibre cloth as a tool for varnish removal -- Can Cellulosebeads save the Circling of the Planets? Cellulose-based consolidating filler to stabilise lifted brittle flakes on a large painting.
Keywords: Materials -- Analysis; Analytical chemistry; Cultural property; Spectrum analysis; Surfaces (Technology).; Thin films; Nanotechnology; Characterization and Analytical Technique; Analytical Chemistry; Cultural Heritage; Spectroscopy; Surfaces, Interfaces and Thin Film; Nanotechnology